Impact of the Daily Intake of Powder of the Moringa Oleifera Leaf on the Evolution of CD4 in the Elderly Aged 18 and Over Living with HIV AIDS in Sarh/Chad - SACRAMENTO, Isabelle; BEHANZIN, GBÉSSOHÈLÈ JUSTIN (My University, 2023)
Malnutrition is a common clinical problem in patients infected with HIV and causes immune suppression and depletion of CD4 T cells. The powder from the leaves of Moringa oleifera (MO) through numerous studies has shown nutritional and therapeutic virtues. Also the administration of this vitamin complex associated with mineral salts to a patient would be simple and practical than that of conventional micronutrients. The objective of this study was to measure the impact of the daily intake of Moringa oleifera leaf powder on the cells of the immune system, more particularly the CD4 T lymphocytes (CD4 LT) of people aged 18 years and over living with HIV AIDS at Notre Dame des Apôtres Maingara Hospital in Sarh / Chad. This was a comparative case-control study that took place over a period of six (06) months. The study included 100 undernourished people living with HIV / AIDS aged 18 or under followed at the level of the People Living with Human Immunodeficiency Virus (PLWHIV) department. Patients were enrolled in two groups. Each patient received 15g / day of Moringa oleifera leaf powder (group A) or NDA enriched flour (group B) during the 6 months. The patients also benefited from a clinical followup (with the measurement of the biological parameters (CBC, TCD4 lymphocytes) at inclusion and after six months. The results obtained showed that there was a nutritional recovery of 52.97 % for the groups supplemented with Moringa oleifera leaf powder versus 20.23% for the enriched flour NDA. We also observed no statistically significant difference in the mean of lymphocytes in group B (enriched flour NDA) (p0.975) The improvement in the CD4 LT count observed in patients supplemented with Moringa oleifera also reflects an improvement in the immune status of PLHIV which is normally in decline after infection with HIV oxidative stress. These micronutrients (vitamins, Mg, phycocyanin) have immuno stimulatory properties which would allow a gain or stabilization of the number of CD4 lymphocytes in groups supplemented with Moringa oleifera leaf powder. Analysis of the blood count reveals that the consumption of M. oleifera allowed a significant increase (p≤ 0.000) in the values of red blood cells (RBC), hemoglobin level (THb), hematocrit (Hte) and (p≤ 0.001) of the mean globular volume (MCV) as well as the parameters of the leukocyte line (macrophages, monocytes and dendritic cells which express this CD4 receptor) which are also major players in the immune system. In control subjects, blood count parameters did not change significantly. Moringa Oleifera leaf powder is said to offer enormous benefits in nutritional recovery (weight gain), stabilization or gain of lymphocytes thus contributing to the well-being of PLHIV.
Keywords: Undernutrition; Moringa oleifera; NDA enriched; flour; CD4 T lymphocytes; people infected with HIV / AIDS; (PLHIV).